Mothers' perceptions of the development of premature newborns - Souza Silva, Jamille (2025)
Introduction: Despite advances in research on child development, there is a scarcity of studies addressing mothers’ perceptions of this process in premature newborns. This represents a significant knowledge gap, as child development is influenced by biological, social, and environmental factors, and prematurity may compromise this journey. Objective: To describe mothers’ perceptions of child development in premature newborns. Methods: A descriptive and exploratory study with a qualitative approach, conducted in a general hospital in Southwestern Bahia, Brazil, with the participation of 15 mothers of premature infants selected by convenience sampling. Data were collected through semi-structured interviews and analyzed using Bardin’s content analysis method and the IRAMUTEQ software. Results: Mothers associated child development with physical growth, developmental stages, and feeding. Their perceptions highlighted motor and cognitive progress, but they also recognized delays, especially in motor and language skills. Strategies such as playful and sound stimulation, and tummy time were identified as promoting development, although the lack of adequate guidance during the hospital stay was mentioned as an obstacle. Conclusion: Maternal perceptions reveal a partial understanding of child development and suggest the need for educational guidance and continuous support for mothers to optimize the development of premature infants in the home environment.